2020
DOI: 10.11591/eei.v9i3.1717
|View full text |Cite
|
Sign up to set email alerts
|

Adoption of technology on E-learning effectiveness

Abstract: The incorporation of E-learning in both private and public tertiary education can help expedite the learning process. The utilization of fast-paced technology with E-learning also allows for a more flexible and convenient learning process. E-learning platforms can be accessed anywhere as long as there is an internet connection, including at home, the workplace, restaurants or while travelling. This allows for the benefit of distance learning. As such, the current study aims to examine the factor effectiveness … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 16 publications
1
10
0
Order By: Relevance
“…Raza et al (2018) also found that both ease of use and usefulness significantly impact the attitudes of university students who believe that e-learning is easy and useful, hence they are more likely to use such devices in their learning process. With e-learning, the use of technology allows for a more flexible and easy learning process because platform can be accessed from anywhere with an internet connection, that is, whether at home, on campus, or on the go (Denan et al, 2020). As a result, it logical to infer that a first year regular graduate student's attitude, as well as antecedent beliefs, improve their desire to adopt the LMS of the University of Education, Winneba for learning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Raza et al (2018) also found that both ease of use and usefulness significantly impact the attitudes of university students who believe that e-learning is easy and useful, hence they are more likely to use such devices in their learning process. With e-learning, the use of technology allows for a more flexible and easy learning process because platform can be accessed from anywhere with an internet connection, that is, whether at home, on campus, or on the go (Denan et al, 2020). As a result, it logical to infer that a first year regular graduate student's attitude, as well as antecedent beliefs, improve their desire to adopt the LMS of the University of Education, Winneba for learning.…”
Section: Discussionmentioning
confidence: 99%
“…LMS can help improve overall student performance (Magalhães et al, 2020), since students can now study off-campus without the requirement for face-to-face or lecturer-student interaction (Masud, 2016). By their nature, LMS speed up the learning process (Denan et al, 2020) and logically increase students on task behaviour. The researchers argue that the graduate students of the university would only reap the enumerated benefits if only they could afford the cost of data bundles.…”
Section: Introductionmentioning
confidence: 99%
“…During pandemics, trust leads to situational awareness, which leads to readiness, impacting the adoption of distance learning practices. Hence, the adoption of technology practices allows for a more flexible and convenient learning process ( Denan, 2020 ) and maintains social distancing amid COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…It could be that perceived usefulness and perceived ease of use are other factors outside of task characteristics, technology characteristics, and individual characteristics that affect the tasktechnology fit [24]. Furthermore, research by Denan [25] shows that student characteristics (individual), characteristics, and technology have a comparative influence on the effectiveness of e-learning. It could be that other factors that are influenced by task characteristics, technology characteristics, and individual characteristics are the effectiveness of e-voting on student council elections.…”
Section: The Relationship Between Task Characteristics Technology Characteristics and Individual Characteristics With Task-technology Fitmentioning
confidence: 99%